Bi-amalgamated algebra with (n; p)-weakly clean like properties - A Aruldoss; Selvaraj Chelliah (Ratio Mathematica, 2023)
Let f : A −→ B and g : A −→ C be two ring homomorphisms and let K and K′ be two ideals of B and C, respectively such that f −1(K) = g−1(K′). In this paper, we give a characterization for the bi-amalgamation of A with (B, C) along (K, K′) with respect to (f, g) (denoted by A ▷◁f,g (K, K′)) to be a (n, p)-weakly clean ring.